Bilateral Trading in Networks - Condorelli, Daniele; Galeotti, Andrea; Renou, Ludovic (Review of Economic Studies, 2017)
In many markets, goods flow from initial producers to final customers travelling through many layers of intermediaries and information is asymmetric. We study a dynamic model of bargaining in networks that captures these features.We show that the equilibrium price demanded over time is non-monotonic, but the sequence of transaction prices declines over time, with the possible exception of the last period. The price dynamic is, therefore, reminiscent of fire-sales and hot-potato trading. Traders who intermediate the object arise endogenously and make a positive profit. The profit-earning intermediaries are not necessarily traders with many connections; for the case of multilayer networks, they belong to the path that reaches the maximum number of potential buyers using the minimal number of intermediaries. This is not necessarily the path of the network that maximizes the probability of consumption by traders who value the most the object (i.e. welfare).